Basic Ionic Liquid as Catalyst in Synthesis of Dimethyl 4-(2-(2, 6-Bis(methoxycarbonyl)pyridine-4-yl)vinyl)pyridine-2, 6-dicarboxylate. (21st January 2018) - Liu, Xiaobing; Hu, Yulin; Fu, Wei
Abstract : In the lanthanide complexes with some organic ligands, the use of pyridine-2, 6-dicarboxylic acid derivatives as sensitizers was better than using others. In this paper, dimethyl 4-(2-(2, 6-bis(methoxycarbonyl)pyridine-4-yl)vinyl)pyridine-2, 6-dicarboxylate (DVDPA) was synthesized starting from dimethyl 4-(chloromethyl)pyridine-2, 6-dicarboxylate (CMDPA) catalyzed by ionic liquid [bmim]OH. The results indicated that the catalytic system presented the highest catalytic activity in the case of 60°C and 40 min and DVDPA yield of 83% can be obtained when ionic liquid dosage is 10% of reactant. The ionic liquid [bmim]OH can be recycled five times without obviously decreasing the catalytic activity after vacuum drying dehydration and the stability of the yield of DVDPA can be maintained.